Penerapan Strategi Pemasaran Digital Untuk Membangun Kesadaran Merek dan Loyalitas Pelanggan pada Usaha Preloved Cardigan "Wearbylia" - Santi Rimadias; Achmad Nur Faidzi; Alifia Ariliyangtama Ramadhan; Felisia Divayanti; Regina Astutiningtyas; Muhammad Zaky Sheehan (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2026)
Efforts to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the era of digital transformation require entrepreneurs to adopt technology-based marketing strategies effectively and sustainably. This community service activity focuses on the preloved cardigan business "Wearbylia," operating in the Greater Jakarta area. This MSME fashion business faces challenges in building kesadaran merek and maintaining customer loyalty amidst intense digital market competition. Through a structured mentoring program, the community service team encourages a shift in business management patterns from conventional approaches to more planned and measurable digital marketing management. The community service activities include mentoring in designing a weekly content calendar on the TikTok platform with three main content pillars, producing commercial videos based on natural lighting techniques and a hook-transition-CTA structure, implementing moment-based promotional strategies such as flash sales and product bundling, and digitizing the inventory recording system using an integrated spreadsheet. This community service activity utilizes in-depth interviews, direct observation of social media platforms, and mentoring based on partner needs. The results of the program demonstrated significant positive impacts, including improved business owners' ability to produce content independently, a 98% increase in inventory data accuracy, and a 15% to 20% increase in daily sales volume during the mentoring period. Wearbylia's success demonstrates that targeted digital literacy skills can catalyze growth for MSMEs in the fashion sector, while also highlighting the importance of synergy between content innovation, consistent social media management, and operational efficiency as the foundation for business sustainability in the digital economy.